Association between corrected QT interval and long-term cardiovascular outcomes in elderly patients who had undergone endovascular therapy for lower extremity arterial disease - Chang, Yao-Ting; Tzeng, I-Shiang; Jang, Shih-Jung; Liu, Kuan-Liang; Hsieh, Chien-An; Chou, Hsin-Hua; Yeh, Kuan-Hung; Huang, Hsuan-Li, TRENDPAD Study Group (Frontiers in Cardiovascular Medicine, 2023)
Background Population-based studies have reported the association between prolonged corrected QT (QTc) intervals and an increased risk of adverse cardiovascular events. Data regarding the association between longer QTc intervals and incident cardiovascular outcomes in patients with lower extremity arterial disease (LEAD) are scarce. Objective To examine the impact of QTc interval on long-term cardiovascular outcomes in elderly patients with symptomatic LEAD. Methods This cohort study extracted data from the Tzu-chi Registry of ENDovascular Intervention for Peripheral Artery Disease (TRENDPAD) and enrolled 504 patients aged ≥ 70 treated with endovascular therapy for atherosclerotic LEAD from July 1, 2005, to December 31, 2019. The main outcomes of interest were all-cause mortality and major adverse cardiovascular events (MACE). Multivariate analysis was conducted using the Cox proportional hazard model to determine independent variables. We performed interaction analysis between corrected QT and other covariates and Kaplan-Meier analysis to compare the outcome of interest among the groups stratified by the tercile of QTc intervals. Results A total of 504 patients [235 men (46.6%); mean age, 79.9 ± 6.2 years; mean QTc interval, 459 ± 33 msec] entered the final data analysis. We categorized the baseline patient characteristics according to terciles of QTc intervals. During the median follow-up time of 3.15 (interquartile ranges, 1.65–5.42) years, we noted 264 deaths and 145 MACEs. The 5-year rates of freedom from all-cause mortality (71% vs. 57% vs. 31%, P < 0.001) and MACEs (83% vs. 67% vs. 46%, P < 0.001) were significantly different among the tercile groups. Multivariate analysis showed that a 1-SD increase in the QTc interval increased the risk of all-cause mortality [hazard ratio (HR) 1.49, P < 0.001] and MACEs (HR 1.59, P < 0.001) after adjusting for other covariates. The interaction analysis showed that QTc interval and C-reactive protein levels were most strongly associated with death (HR = 4.88, 95% CI 3.09–7.73, interaction P < 0.001) and MACEs (HR = 7.83, 95% CI 4.14–14.79, interaction P < 0.001). Conclusions In elderly patients with symptomatic atherosclerotic LEAD, a prolonged QTc interval is associated with advanced limb ischemia, multiple medical comorbidities, increased risk of MACEs, and all-cause mortality.